Improved Uniformity of TaOx-Based Resistive Random Access Memory with Ultralow Operating Voltage by Electrodes Engineering. (9th April 2020) - Li, Chuang; Wang, Fang; Zhang, Jingwei; She, Yu; Zhang, Zhenzhong; Liu, Lifeng; Liu, Qi; Hao, Yaowu; Zhang, Kailiang
Abstract : TaOX is one of the most promising switching materials for resistive random access memory (RRAM) due to its excellent endurance. In this letter, the TaOX -based RRAM devices with three different electrode structures were designed and fabricated to reduce its operating voltage and improve its uniformity. The ITO/TaOX /TiN device could maintain more than ∼10 4 cycles with high uniformity in low operating voltage (the mean voltages of set and reset were 0.036 V and −0.109 V, respectively), which could be attributed to the oxygens-rich property of ITO electrode and the TiON layer (the naturally formed layer when the TiN layer contacted with oxygens). According to X-ray photoelectron spectroscopy (XPS) characterizations and electrical results, a switching mechanism based on oxygen vacancies concentration gradient was proposed to explain the TaOX -based ultralow operating voltage RRAM device.